ACC-deaminase and EPS Production by Salt Tolerant Rhizobacteria Augment Growth in Chickpea under Salinity Stress - Kumari, Poonam; Khanna, Veena (International Journal of Bio-resource and Stress Management, 2023)
Application of salt tolerant rhizobacteria containing 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase and exopolysachharide activity in salt-affected soil can play an important role in alleviating soil salinity stress during plant growth. Out of 66 rhizobacterial strains screened for ACC-deaminase activity, 29 isolates exhibited growth in DF minimal salt medium supplemented with ACC. In liquid medium, ACC-deaminase positive isolates showed different efficacy to utilize ACC as a sole source of N and their growth ranged from 0.205-0.774 (OD at 600 nm) as compared to negative control (0.025-0.285). Among these, 10 potent isolates tolerant to 0.6M NaCl concentration were evaluated for ACC-deaminase activity and EPS production at different salinity levels (0.2, 0.4, 0.8, 1.0 and 1.2 NaCl). The three most efficient salt-tolerant ACC deaminase and EPS containing isolates, B20b, B20d and B-I were investigated alone and in combination with chickpea nodulating, Mesorhizobium ciceris for their effects on the germination and growth of chickpea under various salinity levels (0, 30, 60, 90 and 120 mM NaCl). The results showed that salinity stress significantly reduced plant growth but inoculation with PGPR enhanced plant growth especially at salinity levels ranging from 30-90 mM NaCl, thus reducing the inhibitory effect of salinity. Combined application of PGPR and Rhizobium was more effective under saline conditions, and the combination B-20d+R was the most efficient for improving seedling growth. Biochemical analysis showed higher accumulation of total sugars and protein in response to salinity stress as a protective mechanism to maintain plant turgor required for growth.